2022
DOI: 10.1155/2022/1820777
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Breast Cancer Based on Optimized Deep Learning Approach

Abstract: Breast cancer is a dangerous disease with a high morbidity and mortality rate. One of the most important aspects in breast cancer treatment is getting an accurate diagnosis. Machine-learning (ML) and deep learning techniques can help doctors in making diagnosis decisions. This paper proposed the optimized deep recurrent neural network (RNN) model based on RNN and the Keras–Tuner optimization technique for breast cancer diagnosis. The optimized deep RNN consists of the input layer, five hidden layers, five drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The study on FNN has claimed accuracy of 99.3% over the limited-size dataset with 32 features. The RNN-based tumor prediction model 16 experimented over the Wisconsin dataset with an accuracy of 93.86%. But the RNN models have the limitations of vanishing gradients and complex training procedures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study on FNN has claimed accuracy of 99.3% over the limited-size dataset with 32 features. The RNN-based tumor prediction model 16 experimented over the Wisconsin dataset with an accuracy of 93.86%. But the RNN models have the limitations of vanishing gradients and complex training procedures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study [16] tried to examine the findings and to analyze several ML approaches for the detecting of BC using the same dataset. Another study [17] proposed an efficient recursive neural network (RNN) approach for BC classification using RNN and -Keras-Tuner‖ enhancement method in which they claimed that, the developed model achieved high performance accuracy. However, the study in [16] showed that Logistic regression classifier beats the other classifiers in predicting BC disease using BC Wisconsin (Diagnostic) data set (BCWD).…”
Section: Literature Reviewsmentioning
confidence: 99%
“…There are many techniques that have been introduced in the field of breast cancer prediction. Techniques such as deep learning [4], machine learning [5], and artificial intelligence [6]. Several ML techniques, including Support Vector Machine [7], Genetic [8], and classification techniques, are used to predict breast cancer.…”
Section: Introductionmentioning
confidence: 99%